Book Review: Delong, J. & Whitehead, J. (2023) You and Your Living-Educational Theory: How to conduct a values-based inquiry for human flourishing. Routledge. - Máirín Glenn; Suresh Nanwani (Educational Journal of Living Theories)
Jack Whitehead is the originator of Living Educational Theory Research and Jacqueline Delong’s doctoral supervisor. Since Delong completed her doctorate in 2002 they have been research colleagues. In this book we are given the opportunity to learn about Whitehead’s seminal work through the lens of Delong’s ‘cultures of inquiry’. A culture of inquiry is a non-hierarchical, democratic space that encourages everyone to voice their thoughts (Delong, 2002). The book is divided into four sections, where the ideas become more complex and are explored to give explanation in greater detail in each section. Parts One and Two are aimed toward beginner researchers and those doing research for a Master’s degree, while Part Three focuses on doctoral studies. Part Four outlines how the authors themselves are engaging with their educational responsibility as global citizens. The book indicates that the reader might learn how to conduct Living Educational Theory Research through leafing through this book. However, this is not just a ‘how to’ book. It is an in-depth study on how Living Educational Theory Research can become a transformative movement contributing to the flourishing of humanity. As one reads through the book, it is clear that Delong and Whitehead are not simply showing the reader how to conduct research – they show that they live the underpinning principles of Living Educational Theory Research in their own lives and encourage readers to do likewise.